UPAYA MENINGKATKAN KETERAMPILAN MENGGIRING PADA SEKOLAH DASAR - Iwan, Fransiskus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this study was to determine the learning outcome dribble with plastic balls in class V students of State Elementary School 06 Weve Bemban Kecamantan South Pinoh Melawi. This research uses research "Classroom Action Research" (Classroom Action Research) with variables: Increased dribble with media modifications plastic balls. Subjects in this study were fifth grade students of State Elementary School 06 Weve Bemban Kecamantan South Pinoh Melawi totaling 32 students ,. This research technique using test and measurement, a test with a grating instrument measuring learning outcomes dribble. Analysis of data using percentages. These results indicate there is an increased herding skills in a football game using a modified plastic ball media in class V students of State Elementary School 06 Weve Bemban Kecamantan South Pinoh Melawi. This is evidenced by the increased skills lead the game of football is pretty good, that in the first cycle with an average value of 74.05 so the increase of 10.48%. while the average value on the second cycle is 82.98, so the increase of 23.80%. Keywords: Modified plastic ball, drove in the game of football.